Whole-Genome DNA Methylation Analysis in Brassica rapa subsp. perviridis in Response to Albugo candida Infection - Tirnaz, Soodeh; Miyaji, Naomi; Takuno, Shohei; Bayer, Philipp E.; Shimizu, Motoki; Akter, Mst. Arjina; Edwards, David; Batley, Jacqueline; Fujimoto, Ryo (Frontiers in Plant Science, 2022)
DNA methylation is an epigenetic mark associated with several mechanisms in plants including immunity mechanisms. However, little is known about the regulatory role of DNA methylation in the resistance response of Brassica species against fungal diseases. White rust, caused by the fungus Albugo candida, is one of the most widespread and destructive diseases of all the cultivated Brassica species, particularly Brassica rapa L. and Brassica juncea (L.) Czern and Coss. Here, we investigate whole-genome DNA methylation modifications of B. rapa subsp. perviridis in response to white rust. As a result, 233 and 275 differentially methylated regions (DMRs) in the susceptible cultivar “Misugi” and the resistant cultivar “Nanane” were identified, respectively. In both cultivars, more than half of the DMRs were associated with genes (DMR-genes). Gene expression analysis showed that 13 of these genes were also differentially expressed between control and infected samples. Gene ontology enrichment analysis of DMR genes revealed their involvement in various biological processes including defense mechanisms. DMRs were unevenly distributed around genes in susceptible and resistant cultivars. In “Misugi,” DMRs tended to be located within genes, while in “Nanane,” DMRs tended to be located up and downstream of the genes. However, CG DMRs were predominantly located within genes in both cultivars. Transposable elements also showed association with all three sequence contexts of DMRs but predominantly with CHG and CHH DMRs in both cultivars. Our findings indicate the occurrence of DNA methylation modifications in B. rapa in response to white rust infection and suggest a potential regulatory role of DNA methylation modification in defense mechanisms which could be exploited to improve disease resistance.